2013
DOI: 10.1002/ase.1358
|View full text |Cite
|
Sign up to set email alerts
|

Intensive mode delivery of a neuroanatomy unit: Lower final grades but higher student satisfaction

Abstract: In 2011, Macquarie University moved to a three-session academic year which included two 13-week sessions (traditional mode) and one seven-week session (intensive mode). This study was designed to compare the intensive and traditional modes of delivery in a unit of undergraduate neuroanatomy. The new intensive mode neuroanatomy unit provided the same quantity and quality of material to the same standard, delivered by the same teachers and over the same total hours, but in a shorter timeframe. All students enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…There is another way to look at this: the students perform to the same level in the intensive mode of delivery regardless of the method used. As we know from our previous research, students do not do as well in intensive mode courses compared with the longer traditional sessions, 2 and therefore, what the results may indicate is the problem is around the short time period of this session, which is difficult in the case of a content heavy subject like neuroanatomy. The use of the flipped classroom requires further research to fully evaluate its value.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…There is another way to look at this: the students perform to the same level in the intensive mode of delivery regardless of the method used. As we know from our previous research, students do not do as well in intensive mode courses compared with the longer traditional sessions, 2 and therefore, what the results may indicate is the problem is around the short time period of this session, which is difficult in the case of a content heavy subject like neuroanatomy. The use of the flipped classroom requires further research to fully evaluate its value.…”
Section: Discussionmentioning
confidence: 83%
“…1 This is especially the case in the intensive mode teaching of a course, which compresses a traditional teaching program into a shorter session. 2 Previously, we conducted a comparison between traditional and intensive modes of delivery of a unit of neuroanatomy, and we found that the final grades were lower in the latter group. 2 This led to the rationale for this present study: to test the ''flipped classroom'' as a possible effective teaching method in the intensive or compressed delivery class.…”
Section: Introductionmentioning
confidence: 95%
“…Wlodkowski et al [ 25 ] report that students’ overall attitudes toward ICs were positive in comparison to semester long courses. Whillier et al [ 26 ] note equivalent findings regarding student satisfaction; whereas, Mishra et al [ 23 ] find students mostly dissatisfied with ICs. It is important to note an absence of comparative research on ICs delivered online versus semester long courses delivered online.…”
Section: Introductionmentioning
confidence: 99%
“…Hall et al [17] report that most studies indicate greater student success in ICs as compared to traditional courses; the remaining studies demonstrate equivalent success. Conversely, Whillier and Lystad conclude that students taught in a traditional mode cohort achieved “significantly higher final grades compared to the intensive mode cohort” [31, p.286]. Regarding test scores, some evidence suggests comparable results [15] or slightly higher results for ICs than traditional courses [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Results related to student satisfaction or attitudes toward ICs are also mixed. Wlodkowski et al [35] report that students’ overall attitudes toward ICs were positive in comparison to traditional courses; Whillier et al [31] note equivalent findings regarding student satisfaction; whereas, Mishra et al [23] find most students unhappy with ICs, noting mostly negative perceptions.…”
Section: Introductionmentioning
confidence: 99%